Nutritional and Culinary Habits to Empower Families (n-CHEF): a feasibility study to increase consumption and home cooking of plant-based foods - Leticia Goni; Luca Simonin; Anacristina Rovayo; Isabella Kury-Guzman; Nerea Martín-Calvo; Miguel Ruiz-Canela (Cambridge University Press, 2024)
Abstract Objective: To analyse the feasibility and acceptability of a culinary nutritional intervention aimed at increasing plant-based foods consumption in the context of the Mediterranean diet in parent-child dyads. Design: The Nutritional and Culinary Habits to Empower Families (n-CHEF) is a 9-month feasibility study that included four culinary nutritional workshops (two face to face, two online) led by a chef and a dietitian-nutritionist. These workshops combined cooking with plant-based foods, with nutritional advice and experimental activities. The main outcomes were retention, quality of the intervention (monitoring workshops, acceptability and perceived impact) and changes in dietary and cooking habits. Setting: Parent-child dyads, Spain. Participants: Parent-child (aged 10-14 years) dyads. Results: Fifteen parent-child dyads were recruited, of which thirteen were retained during the 6-month follow-up. All but one parent-child dyads attended the four workshops. The overall assessment of the workshops was positive, although the online workshops were rated lower than the face to face. In general, parent-child dyads reported benefits in terms of nutrition and cooking aspects. Parents significantly increased their adherence to the Mediterranean diet, but non-significant changes were observed in children. However, children increased their consumption of vegetables and legumes and reduced snacks and ready meals. Parents also changed some of their culinary habits and increased their confidence in cooking at home. Conclusions: The n-CHEF showed that the culinary nutritional intervention had good levels of recruitment, retention and acceptability among parent-child dyads. In addition, dietary and culinary knowledge and habits can be improved, although further studies are needed to know the long-term effects in larger populations.